THE THE INFLUENCE OF JIGSAW'S TYPE OF COOPERATIVE LEARNING MODELS ON IPS RESULTS AT FOUR GRADE STUDENTS IN THE 16TH ELEMENTARY SCHOOL OF BUNGKU - Rifa'i, Abdul; _, Lukman; _, Jamaludin; Gamar, Mahfud M (Jurnal Ilmu Pendidikan Ahlussunnah, 2024)
Research is aims to identify the impact of jigsaw's type of cooperative learning model and the learning style of ips results in 4th grade at 16th elementary school of Bungku. The study aims to find out the impact of the cooperative learning model of the jigsaw type and the learning style on the learning outcomes of social sciences in the fourth grade at 16th Bangku State Elementary School. This research has been discouraged because, in the present day, there are schools that use the method of lectures where learning is only centered on the teacher, making students look bored and sleepy so that the student's learning results are not optimal. This research is a quantitative research type of quasi-experimental design research, with the subject of the study being students of Class Four State Elementary Schools 16th. There are 26 people, consisting of 14 men and 12 women, who are divided into two groups: 13 people in the experimental group and 13 people in the control group. The Descriptive analysis results showed an average increase of 26.3% for the experimental class and 21% for the control class. Based on the test results of the hypothesis, the calculated value is greater than the value in the table with a significance value of 0.05, so H0 is rejected and Ha is accepted. That is, students' learning outcomes are significantly influenced by the cooperative learning model of the jigsaw.